Three-Dimensional Visualization With Tissue Clearing Uncovers Dynamic Alterations of Renal Resident Mononuclear Phagocytes After Acute Kidney Injury - Kim, Kipyo; Kim, Yun-Gyeong; Jung, Su Woong; Kim, Yang Gyun; Lee, Sang-Ho; Kwon, Seung-Hae; Moon, Ju-Young (Frontiers in Immunology, 2022)
Traditional histologic methods are limited in detecting dynamic changes in immune cells during acute kidney injury (AKI). Recently, optical tissue clearing combined with multiphoton microscopy (MPM) or light sheet fluorescence microscopy (LSFM) has become an emerging method for deep tissue evaluation and three-dimensional visualization. These new approaches have helped expand our understanding of tissue injury and repair processes, including tracing the changes in immune cells. We designed this study to investigate the morphological and functional alterations of renal mononuclear phagocytes (MNPs) in lipopolysaccharide (LPS)-induced AKI using renal clearing in CD11c-YFP mice. We also evaluated the effect of the NLRP3 inhibitor MCC950 to determine whether NLRP3 inhibition attenuates the activation of CD11c+ cells in an LPS-induced AKI model. Transverse sectioned whole mouse kidney imaging by LSFM showed that CD11c+ cells were mainly distributed in the cortex, especially the tubulointerstitial area. The number of CD11c+ cells was significantly more densely interspersed, particularly in periglomerular and perivascular lesions, in the saline-treated LPS-exposed kidney than in the control kidney. Deep imaging of the kidney cortex by MPM demonstrated an increased number of CD11c+ cells in the saline-treated LPS group compared with the control group. This quantitative alteration of CD11c+ cells in AKI was accompanied by morphological changes at high resolution, showing an increased number and level of dendrites. These morphological and behavioral changes in the saline-treated LPS group were accompanied by increased MHC class II and CD86 on CD11c-YFP+ cells. MCC950 attenuated the activation of CD11c+ cells after AKI and improved renal function. In conclusion, wide and deep three-dimensional visualization using MPM or LSFM combined with kidney clearing uncovers dynamic changes of renal MNPs, which are directly linked to renal function in AKI.